Pterocactus gonjianii - Kiesling, Roberto (2009)
The cactus geophyte, Pterocactus gonjianii, endemic from San Juan province in the Andes  of Argentina, is ilustrated and its habit and morphological details are described. Botanical and horticultural notes on this unusual genera of opuntioid cacti cacti are also provided.